Konflik Sosial Dalam Novel "Orang-orang Biasa" Karya Andrea Hirata (Kajian Lewis A. Coser) - Kukun, Melania; Jama, Karolus B.; Djokaho, Margareta P.E (Jurnal Lazuardi, 2025)
This research is entitled "Social Conflict in the Novel Ordinary People by Andrea Hirata" Lewis A. Coser Study." The focus of this research is adjusted to the formulation of the problem discussed in this research, namely, how social conflict manifests itself in the novel Orang Ordinary by Andrea Hirata. The theory used in this research is Lewis A. Coser's theory. The method used in this research is a qualitative descriptive method. The results of the research show that there is a form of social conflict contained in the novel Ordinary People by Andrea Hirata. The form of social conflict is in the form of (a) a realistic form of conflict (group). (b) the manifestation of non-realistic (personal) conflict. Things like that happen between the characters in the novel Ordinary People by Andrea Hirata, namely Dinah and her friends. It is known that in the novel Ordinary People by Andrea Hirata, the conflicts that often arise are realistic social conflicts (groups), because the social conflicts that occur in the novel involve two or more people.